Characterization of bacterial cellulose produced by Acetobacter pasteurianus MGC-N8819 utilizing lotus rhizome. (1st August 2022) - Nie, Wenxia; Zheng, Xuan; Feng, Wei; Liu, Ye; Li, Yudong; Liang, Xinle
Abstract: Bacterial cellulose (BC) and its bacterial producers have been employed in valuable applications in the biomaterial, biomedicine and food industries. In this study, three novel strains were isolated from traditional rice vinegar and confirmed to be capable of producing BC, among which Acetobacter pasteurianus MGC-N8819 exhibited a relative high BC yield of 6.6 g/L in the Hestrin-Schramm (HS) medium. Furthermore, the agricultural lotus rhizome and its byproducts were investigated as an alternative source for BC synthesis by the novel strain. The combination of alpha-amylase and glucoamylase treatments effectively increased the release of the reduced sugar from rhizome byproducts, achieving a BC yield of 2.1 g/L and BC productivity of 0.26 g/(L·day). Though the BC yields of rhizome media were lower than that of the control HS medium, the rhizome-derived BC exhibited much better quality with great fiber diameter (57 nm), high crystallinity index (90.5%), tensile strength (82 MPa), elongation at break (26%) and thermal stability, indicating that the rhizome media promoted both the bacterial growth and specific BC synthesis. A. pasteurianus MGC-N8819 represents a valuable candidate for BC production and lotus rhizome byproducts can be reutilized for valuable BC production, which promises the wastes reduction during the lotus rhizome-related food processes. Highlights: The bacterial cellulose (BC) producer A. pasteurianus isolated from abnormal vinegar. Lotus rhizome byproducts utilized as alternative carbon source for BC synthesis. Rhizome media-treated with mixed enzymes improved the BC productivity and quality. A. pasteurianus and rhizome-derived BC promise a better potential of applications.